You're not you [videorecording (DVD)] - Swank, Hilary; Rossum, Emmy, 1986-; Duhamel, Josh, 1972-; Wildgen, Michelle (Entertainment One, 2015)
When an accomplished pianist is diagnosed with the devastating and incurable disease ALS, she hires a directionless young woman who becomes her full-time caregiver. Complete opposites, the strangers form a life changing bond inspiring each other to live life to fullest, while being brought together by the most challenging of circumstances.